2018
DOI: 10.1039/c8cc01584h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterisation and antiproliferative activity of a new fluorescent 4-amino-1,8-naphthalimide Tröger's base–Ru(ii)–curcumin organometallic conjugate

Abstract: The synthesis, photophysics and biological investigation of fluorescent 4-amino-1,8-naphthalimide Tröger's bases (TB-1-TB-3) and a new Tröger's base p-cymene-Ru(ii)-curcumin organometallic conjugate (TB-Ru-Cur) are described; these compounds showed fast cellular uptake and displayed good luminescence and cytotoxicity against cervical cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…), the ISC of Tröger's bases has not been reported. Recently an NI‐derived Tröger's base/Ru II –curcumin organometallic conjugate was demonstrated to show cytotoxicity against cervical cancer cells, but the phototoxicity and the ISC of the base itself were not studied …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), the ISC of Tröger's bases has not been reported. Recently an NI‐derived Tröger's base/Ru II –curcumin organometallic conjugate was demonstrated to show cytotoxicity against cervical cancer cells, but the phototoxicity and the ISC of the base itself were not studied …”
Section: Introductionmentioning
confidence: 99%
“…Recently an NI-derived Trçger's base/Ru II -curcumin organometallic conjugate was demonstrated to showc ytotoxicity against cervical cancer cells, but the phototoxicitya nd the ISC of the base itselfw ere not studied. [41] On the basis of these previous studies on Trçger's bases, that is, the quenching of the fluorescencei np olar solvents and the orthogonal geometry,w es upposed that SOCT-ISC may occur in Trçger's bases through symmetry-breaking CT (SBCT), that is, one NI moiety in the Trçger's base acts as the electron donor,a nd the othera st he electron acceptor. [42] Herein, we propose using the rigid, almosto rthogonal geometry of the two subunits in Trçger's base to implement SOCT-ISC.…”
Section: Introductionmentioning
confidence: 99%
“…A DNA docking study of this complex revealed the same mechanism of action as in platinum chemotherapy. The Ru(II) complex with Tröger’s base, p-cymene, and curcuminato ligands shows fast cellular uptake and displays good luminescence and cytotoxicity against cervical cancer cells [27]. Platinum(II) complexes with curcuminate can act as chemotherapeutic agents which release photoactive curcumin and an active Pt(II) species upon irradiation with visible light [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, the core ingredient of turmeric, is known to have a broad range of pharmacological properties and is a popular antimicrobial, antidiabetic, anti‐inflammatory, anticancer, and antioxidant agent [26] . Also, the intrinsic green fluorescence of curcumin was used as an optical biomarker [27] . Though curcumin has a wide range of applications, but its poor solubility in water limits its bioavailability and pharmacological potential [28] .…”
Section: Resultsmentioning
confidence: 99%
“…[26] Also, the intrinsic green fluorescence of curcumin was used as an optical biomarker. [27] Though curcumin has a wide range of applications, but its poor solubility in water limits its bioavailability and pharmacological potential. [28] We have shown previously that the hydrophobic interior of the cage 1 can efficiently encapsulate curcumin [18] and we found that, 15 μM cage 1 can encapsulate 16.3 μM of curcumin (Supporting Information).…”
Section: Antibacterial Activity Against Mrsamentioning
confidence: 99%